Fast Recovery 3D Fast Spin-Echo MR Imaging of the Inner Ear at 3 T - Naganawa, Shinji; Koshikawa, Tokiko; Fukatsu, Hiroshi; Ishigaki, Takeo; Aoki, Ikuo; Ninomiya, Ayako (American Journal of Neuroradiology, 2002)
Summary: High-resolution MR imaging of the inner ear with a heavily T2-weighted 3D fast spin-echo sequence has been performed successfully at 1.5 T. However, at 3 T, the longer T1 time of CSF necessitates a longer TR, resulting in significantly prolonged imaging times. In this study, the fast recovery 3D fast spin-echo sequence, which permits the TR to be reduced while maintaining T2 contrast, was optimized at 3 T for imaging of the inner ear. The optimized sequence parameters are as follows: 1500/294 (TR/TE); echo spacing, 18.1 ms; bandwidth, 38 kHz at 512 readout; and imaging time, 13 minutes.